2010
DOI: 10.4161/cbt.9.1.10340
|View full text |Cite
|
Sign up to set email alerts
|

CT response assessment combining reduction in both size and arterial phase density correlates with time to progression in metastatic renal cancer patients treated with targeted therapies

Abstract: Original article can be found at: http://www.landesbioscience.com/journals/cbt/ Copyright Landes Bioscience [Full text of this article is not available in the UHRA]Background: Response assessment is critical in evaluating effectiveness of anticancer treatment. Tyrosine kinase inhibitors (TKIs) in renal cell carcinoma (RCC) are associated with significant clinical benefit but may not result in significant tumour size reduction. Thus standard size-based response assessment with RECIST is insensitive, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 13 publications
2
65
3
1
Order By: Relevance
“…However, cancers treated with sorafenib often show little change in size during early stage of therapy despite substantial clinical benefit. Radiologic criteria that additionally take into account functional changes in the enhancement of lesions on contrast materialenhanced CT scans or dynamic contrast-enhanced MRI have helped to identify patients who went on to show clinical benefit as early as 9 weeks into treatment [16][17][18]. Accordingly, studies on molecular markers in evaluation of metastatic RCC treatment are relevant.…”
Section: Discussionmentioning
confidence: 99%
“…However, cancers treated with sorafenib often show little change in size during early stage of therapy despite substantial clinical benefit. Radiologic criteria that additionally take into account functional changes in the enhancement of lesions on contrast materialenhanced CT scans or dynamic contrast-enhanced MRI have helped to identify patients who went on to show clinical benefit as early as 9 weeks into treatment [16][17][18]. Accordingly, studies on molecular markers in evaluation of metastatic RCC treatment are relevant.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical settings, there is also radiological evidence of necrosis induced by anti-angiogenic drugs in patients with metastatic renal cell carcinoma. In addition, radiological criteria combining changes in tumor density and in tumor size [16][17] distinguish prognostic groups better than the standard criteria that only assess changes in tumor size [18] . As necrosis is an indirect marker of hypoxia, we decided to study the in vitro effect of experimental hypoxia on renal cancer stem cells sorted from these renal cell carcinoma xenografts.…”
Section: Research Highlightmentioning
confidence: 99%
“…However, it has also been shown that a 10% reduction in the sum of largest diameters is a better predictor than the Choi criteria [10] . Using modified Choi criteria (a decrease in size 410% and a decrease in tumour attenuation 415%), Nathan et al [16] showed that such estimation is better correlated to time to progression than the Choi criteria. When contrast attenuation-based criteria are applied, standardization of the contrast phases is crucial.…”
Section: Morphological Imagingmentioning
confidence: 99%